Measurement sequences for magic state distillation - Haah, Jeongwan; Hastings, Matthew (Quantum, 2021)
Magic state distillation uses special codes to suppress errors in input states, which are often tailored to a Clifford-twirled error model. We present detailed measurement sequences for magic state distillation protocols which can suppress arbitrary errors on any part of a protocol, assuming the independence of errors across qubits. Provided with input magic states, our protocol operates on a two-dimensional square grid by measurements of ZZ on horizontal pairs of qubits, XX on vertical pairs, and Z,X on single qubits.